Reconstructing the Concept of Riba from the Perspective of Contemporary Islamic Jurisprudence: An Approach to Modern Islamic Scholars' Thought - Faridah , Faridah; Wafa, Faqih El; Rizali , Muhammad (Innovative: Journal Of Social Science Research, 2024)
This study explores the reconstruction of the concept of riba from a contemporary fiqh perspective to understand how modern interpretations can adapt to global economic developments. The primary goal is to compare traditional and contemporary views on riba and analyze the contribution of contemporary thought in the current economic context. The research employs a literature review, including the analysis of works by classical and contemporary scholars and relevant Islamic financial instruments. The findings indicate that contemporary scholars use a more flexible and contextual approach, focusing on justice and the prevention of exploitation. The maqasid al-sharia approach is applied to evaluate financial transactions, enabling the development of innovative Islamic financial instruments like sukuk, mudharabah, and murabahah. These findings have significant implications for both fiqh theory and Islamic financial practice, providing a more dynamic and adaptive framework to meet modern economic needs.